Influência da mistura gasosa e da temperatura no processo de nitrocarbonetação a plasma do aço DIN 100Cr6 - Fontes, Marcos Alves (Universidade Federal de São Carlos, 2018)
The surface treatments of metal alloys allow improving the surface qualities by the deposition of another material or by surface modification, producing coatings. The nitrocarburizing, considered one of the most important thermochemical treatments, involves the simultaneous diffusion of N and C into the surface. Understanding and controlling the formation of the nitrocarburized layer have considerable industrial interest due to the improvements regarding wear, fatigue, and corrosion resistances on the metals and their alloys. In the present work, surface modification by plasma nitrocarburizing was performed in a DIN 100Cr6 steel. The studied process parameters were the treatment temperature (550 and 600°C) and methane concentration in the gas mixture (0, 1.0, 1.5, and 2.0%), whereas the treatment time was fixed in 2h. X-ray diffraction (XRD), scanning electron microscopy (SEM), and energy dispersive spectroscopy (EDS) analyses, as well as wear resistance and micro-hardness tests were used to characterize the samples. The results show that the modifications on the material surface considerably improve the mechanical properties such as hardness and wear resistance, by the formation of nitrides. The compound layer composition and morphology are quite sensitive to the temperature and chemical composition of the treatment atmosphere. Increasing the CH4 concentration on the gas mixture contributes to the formation of the epsilon-Fe2-3 (C,N) phase, considerably enhancing the wear resistance and microhardness, and the use of high N2 concentration induces the production of a micro-porosity layer. Ferritic nitrocarburizing promotes thinner micro-porosity and compound layers, with predominant epsilon phase, and higher superficial microhardness, and the austenitic nitrocarburizing produces a thicker micro-porosity and compound layers, with predominant epsilon and gama’-Fe4N phases on the compound layer.
Influence of the gas mixture and temperature on the plasma nitrocarburizing process of the DIN 100Cr6 steel
Keywords: Nitrocarbonetação; Microdesgaste; Microdureza; Nitrocarburizing; Micro-wear; Microhardness; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA DE TRANSFORMACAO